Comparative transcriptome analysis of canola carrying a single vs stacked resistance genes against clubroot - Wen, Rui; Song, Tao; Gossen, Bruce D.; Peng, Gary (Frontiers in Plant Science, 2024)
Pyramiding resistance genes may expand the efficacy and scope of a canola variety against clubroot (Plasmodiophora brassicae), a serious threat to canola production in western Canada. However, the mechanism(s) of multigenic resistance, especially the potential interaction among clubroot resistance (CR) genes, are not well understood. In this study, transcriptome was compared over three canola (Brassica napus L.) inbred/hybrid lines carrying a single CR gene in chromosome A03 (CRa M , Line 16) or A08 (Crr1 rutb , Line 20), and both genes (CRa M +Crr1 rutb , Line 15) inoculated with a field population (L-G2) of P. brassicae pathotype X, a new variant found in western Canada recently. The 16 was susceptible, while lines 15 and 20 were partially resistant. Functional annotation identified differential expression of genes (DEGs) involved in biosynthetic processes responsive to stress and regulation of cellular process; The Venn diagram showed that the partially resistant lines 15 and 20 shared 1,896 differentially expressed genes relative to the susceptible line 16, and many of these DEGs are involved in defense responses, activation of innate immunity, hormone biosynthesis and programmed cell death. The transcription of genes involved in Pathogen-Associated Molecular Pattern (PAMP)-Triggered and Effector-Triggered Immunity (PTI and ETI) was particularly upregulated, and the transcription level was higher in line 15 (CRa M + Crr1 rutb ) than in line 20 (Crr1 rutb only) for most of the DEGs. These results indicated that the partial resistance to the pathotype X was likely conferred by the CR gene Crr1 rutb for both lines 15 and 20 that functioned via the activation of both PTI and ETI signaling pathways. Additionally, these two CR genes might have synergistic effects against the pathotype X, based on the higher transcription levels of defense-related DEGs expressed by inoculated line 15, highlighting the benefit of gene stacking for improved canola resistance as opposed to a single CR gene alone.